19 Optimal assessment and monitoring of SLE patients in clinical practice. (1st September 2020) - Voskuyl, Alexandre
Abstract : Systemic lupus erythematosus (SLE) is a heterogeneous disease, characterised by a wide spectrum of clinical manifestations (ranging from arthritis and skin manifestations to renal insufficiency or central nervous system involvement) with an unpredictable relapsing-remitting course. SLE primarily affects young women in their childbearing lifetime, and perinatal complications due to SLE and/or the coexistence of the presence of antiphospholipid antibodies, can occur. Also, low complement levels and many antibodies can be found in SLE, among which anti-ds DNA and anti-Sm. During the disease course, irreversible organ damage can accrue due to SLE and/or its treatment. In addition, comorbidities can develop, including infections, osteoporosis and atherosclerosis. Compared to the general population, quality of life is reduced, frequently due to severe fatigue or psychological issues, amongst other reasons. As such reduced work capacity and/or work loss may occur. So, how should we assess and monitor patients with SLE? 1 2 The (frequency of) assessments depends on the stage of disease (diagnosis and follow-up). Disease activity (active disease [i.e. every 1–3 months] versus stable disease [i.e. every 6–12 months]), and specific conditions (i.e. pregnancy, thrombosis and bone fractures). Measuring disease activity with validated instruments (i.e. SLEDAI-2k, BILAG 2004) at each visit is recommended, in addition to a history and clinical examination, laboratory assessments (including blood, urine and immunology test) and eventually other investigations (i.e. imaging or biopsy); using these instruments results in better outcome, although the evidence is of low-moderate quality. However, high disease activity is associated with poor outcome (higher mortality rate, higher level of organ damage and comorbidities). Conversely, lower levels of disease activity and remission are associated with better outcome. It is important that clinical symptoms can be due to one or any combination of the following: disease activity, thrombosis or active inflammation, drug toxicity, chronic damage due to the disease or to its treatment, or to comorbidity (i.e. infection). Yearly assessment of disease damage (with SLICC Damage Index, SDI) is recommended, although the evidence of better outcome is of low-moderate quality. However, early and late damage is associated with small to moderate increase in mortality, further damage in the future and reduced quality of life and therefore is justified to assess. Regular assessment of cardiovascular (CV) risk factors in particular as well as corticosteroid-associated adverse events is recommended, with moderate-high quality evidence for CV assessment. The rationale and principles of treat-to-target (T2T) in SLE and how to incorporate T2T in daily clinical practice will be discussed. 3–5 Learning Objectives: Describe the relevance of systematic assessment of disease activity, disease damage, comorbidities and quality of life Explain the current clinical practice guidelines in SLE, and define unmet needs in order to improve our daily practice Discuss the current state of T2T in SLE References: Gordon C, Amissah-Arthur MB, Gayed M, et al . The British Society for Rheumatology guideline for the management of systemic lupus erythematosus in adults: Executive Summary. Rheumatology (Oxford) 2018;57(1) :14–18. Keeling SO, Alabdurubalnabi Z, Avina-Zubieta A, et al . Canadian Rheumatology Association Recommendations for the Assessment and Monitoring of Systemic Lupus Erythematosus. J Rheumatol 2018;45(10) :1426–39. Fanouriakis A, Kostopoulou M, Cheema K, et al . 2019 Update of the Joint European League Against Rheumatism and European Renal Association-European Dialysis and Transplant Association (EULAR/ERA-EDTA) recommendations for the management of lupus nephritis. Ann Rheum Dis 2020;79(6) :713–23. Golder V, Kandane-Rathnayake R, Hoi AY, et al . Association of the lupus low disease activity state (LLDAS) with health-related quality of life in a multinational prospective study. Arthritis Res Ther 2017;19(1) :62. van Vollenhoven R, Voskuyl A, Bertsias G, et al . A framework for remission in SLE: consensus findings from a large international task force on definitions of remission in SLE (DORIS). Ann Rheum Dis 2017;76(3) :554–61.